Guide for the observational control of offensive group tactics in soccer/Guía para el control observacional de la táctica grupal ofensiva en el fútbol - Pablo Raidel González Ramos; Osvaldo Javier Martín Agüero; José Guillermo Montero Quesada; Dayron Alberto Rice Nelson (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2022)
Observational control models are used to carry out studies of opponents, allowing the tactical strategist to detect and plan a group of actions according to the weaknesses and strengths of the opponents. The objective of this research was to make a guide for observational control on offensive group tactics in soccer for analysts and coaches of this sport. Methods such as experiential experience, observation, documentary review and reflective critical opinion workshops were used. A non-probabilistic discretional sampling was used where the arguments were elaborated by 20 members of the International Group for the Preparation, Rehabilitation, Recreation and Research and Improvement in Soccer disciplines; these professors, analysts and soccer coaches belong to the Universities of Camagüey and Las Tunas. Two observation guides were made for the games and another one for the soccer training, both in function of the observational control of the offensive group tactics. It was verified the application of the elaborated observational guides that allow knowing the depth with which the soccer players manage to form and externalize the tactical habits during the game.